Favorable effect of renal denervation on elevated renal vascular resistance in patients with resistant hypertension and type 2 diabetes mellitus - Manukyan, Musheg; Falkovskaya, Alla; Mordovin, Victor; Pekarskiy, Stanislav; Zyubanova, Irina; Solonskaya, Ekaterina; Ryabova, Tamara; Khunkhinova, Simzhit; Vtorushina, Anastasia; Popov, Sergey (Frontiers in Cardiovascular Medicine, 2022)
Objective: To assess the effect of renal denervation (RDN) on renal vascular resistance and renal function in patients with drug-resistant hypertension (HTN) and type 2 diabetes mellitus (T2DM). Methods: Fifty-nine patients (mean age 60.3 ± 7.9 years, 25 men) with resistant HTN (mean 24 h blood pressure [BP] 158.0 ± 16.3/82.5 ± 12.7 mmHg, systolic/diastolic) and T2DM (mean HbA1c 7.5 ± 1.5%) were included in the single-arm prospective study and underwent RDN. Renal resistive index (RRI) derived from ultrasound Doppler flowmetry; estimated glomerular filtration rate (Chronic Kidney Disease Epidemiology Collaboration formula) and office and 24 h BP were measured after RDN was assessed at baseline and at 6 and 12 months to evaluate the respective changes in renal vascular resistance, renal function, and BP during treatment. Results: Forty-three patients completed twelve months follow-up. The RRI varied depending on the baseline value. Specifically, the RRI decreased significantly in patients with elevated baseline RRI values ≥ 0.7 (n = 23; -0.024 [95% confidence interval (CI): -0.046, -0.002], p = 0.035) and did not change in those with baseline RRI < 0.7 (n = 36; 0.024 [95% CI: -0.002, 0.050], p = 0.069). No significant change was observed in eGFR whereas BP was significantly reduced at 12 months after RDN by -10.9 (95% CI: -16.7, -5.0)/-5.5 (95% CI: -8.7, -2.4) mmHg, systolic/diastolic. No relationship was found between the changes in RRI and BP. Conclusions: Our study shows that RDN can decrease elevated renal vascular resistance (RRI > 0.7) and stabilize kidney function in patients with RHTN and T2DM independently of its BP-lowering effect.